Perancangan Sistem Informasi Peminjaman Buku Diperpustakaan Menggunakan Bahasa Pemrograman PHP Dan Database Mysql - Regina Adelia Regina Adelia (Jurnal Teknologi, 2020)
Web design of borrowing books at SMAN 1 Lembah Melintang PasamanBarat Library aims to make it easier for librarians to enter books that were previously done manually, thus saving time. In this application I make it easy for library staff to do computerized input so that it can be efficient and effective. Application of SMAN 1 Valley Melintang Valley Pasaman Barat Library. The library makes it easy for library staff to enter new book data, member data and employee data at SMAN 1 Lembah Valley Pasaman Barat Library. Book data that has been inputted is stored with a MySQLdatabase so that the data is safe.This research helps in establishing a book loan system. The design system in making a book loan application at SMAN 1 Lembah Melintang Pasaman Barat was developed by using some software namely Xampp, Sublime Text, Server which is a combination of Web Server, PHP and MySQL.